A rescuer's story : Pastor Pierre-Charles Toureille in Vichy France - Zasloff, Tela (University of Wisconsin Press, 2003)
"This is the story of Pierre Toureille, a French Protestant pastor whose efforts resulted in the rescue of hundreds of refugees, most of them Jewish. Inspired by his Huguenot heritage, Pastro Toureille participated in international Protestant church efforts to combat Nazism during the 1930s and headed a major refugee aid organization in Vichy France during World War II. After the war, Pastor Toureille was honored by the Jewish organization Yad Vashem as one of the "Righteous Among the Nations."" "In telling Toureille's story, Tela Zasloff also describes the wide-ranging network of Protestant pastors and lay people in southern French villages who participated in an aggressive rescue effort. She delves into their motivations, including their heritage as members of a religious minority. Toureille's rescue work under the Vichy regime, partly official and then increasingly clandestine as the war progressed, was a crucial part of the French nonviolent "spiritual resistance" against Nazism."--Jacket